2018
DOI: 10.1108/jfc-10-2016-0062
|View full text |Cite
|
Sign up to set email alerts
|

Pyramids, Ponzis and fraud prevention: lessons from a case study

Abstract: Purpose This paper aims to empirically identify factors that increase consumer vulnerability to pyramid scheme fraud and compares/contrasts dynamics and implications of pyramid and Ponzi fraud. Design/methodology/approach Statistical techniques, including multiple regression, are used to analyze participant data (with over half a million individuals) from a now-defunct US-based pyramid scheme, Fortune Hi-Tech Marketing. Findings Findings suggest that this pyramid scheme flourished in counties with identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 17 publications
(38 reference statements)
0
21
0
1
Order By: Relevance
“…The lack of knowledge of the sophistication and how Ponzi schemes operate to defraud unsuspecting victims of their savings requires the regulators of financial markets to intensify education of investors on how to identify and avoid Ponzi schemes (Amoah, 2018). Bosley and Knorr (2018) suggested that the state and federal regulators should allocate resources and to actively engage in preventive education. In a similar line, Galasintu, Supanit, and Chaiittivej (2018) suggested that consumers must be self-regulated by becoming more aware of business fraud and learn to be more protective.…”
Section: Prevention Measures Of Ponzi Schemesmentioning
confidence: 99%
“…The lack of knowledge of the sophistication and how Ponzi schemes operate to defraud unsuspecting victims of their savings requires the regulators of financial markets to intensify education of investors on how to identify and avoid Ponzi schemes (Amoah, 2018). Bosley and Knorr (2018) suggested that the state and federal regulators should allocate resources and to actively engage in preventive education. In a similar line, Galasintu, Supanit, and Chaiittivej (2018) suggested that consumers must be self-regulated by becoming more aware of business fraud and learn to be more protective.…”
Section: Prevention Measures Of Ponzi Schemesmentioning
confidence: 99%
“…In particular, those pursuing business or economics degrees may see this type of opportunity as more in line with their skills and interests. We capture self‐reported degree of religiosity using a question from the Pew Religious Landscape Study (Pew Research Center ) for two reasons: MLM often appeals to religious consumers (Bromley ; Luca ) and religiosity has been found to play a role in consumer vulnerability to financial fraud (Bosley et al ; Bosley and Knorr ; Consumer Fraud Research Group ).…”
Section: Experimental Frameworkmentioning
confidence: 99%
“…The case study approach allows for a more holistic inquiry that seeks to be exploratory, explanatory and descriptive [ 57 ] in order to drive a causal investigation [ 58 ]. Case study analysis is an accepted method for considering business fraud [ 59 , 60 , 61 ]. A limitation of this approach is the risk of selection bias, and this is considered in the analysis of the findings.…”
Section: Methodsmentioning
confidence: 99%